Dampening Global Financial Shocks : Can Macroprudential Regulation Help (More than Capital Controls)? - Bergant, Katharina; Grigoli, Francesco; Hansen, Niels-Jakob.; Sandri, Damiano (Washington, D.C. : International Monetary Fund, 2020)
We show that macroprudential regulation can considerably dampen the impact of global financial shocks on emerging markets. More specifically, a tighter level of regulation reduces the sensitivity of GDP growth to VIX movements and capital flow shocks. A broad set of macroprudential tools contribute to this result, including measures targeting bank capital and liquidity, foreign currency mismatches, and risky forms of credit. We also find that tighter macroprudential regulation allows monetary policy to respond more countercyclically to global financial shocks. This could be an important channel through which macroprudential regulation enhances macroeconomic stability. These findings on the benefits of macroprudential regulation are particularly notable since we do not find evidence that stricter capital controls provide similar gains.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet